Prevalence and concurrent correlates of FAI-screened symptoms suggestive of temporomandibular disorders among dental students: a cross-sectional study - Sena Camcıoglu Yurtseven; Hakan Gurcan Gurel (BMC Oral Health, 2026)
Abstract Background Temporomandibular disorders (TMDs) are multifactorial conditions involving the temporomandibular joints, masticatory muscles, and associated structures. Dental students may experience stressors and parafunctional behaviors relevant to TMD symptom screening. This study aimed to estimate the prevalence and distribution of Fonseca Anamnestic Index (FAI)-screened symptoms suggestive of TMD among dental students and to examine concurrent demographic, stress-related, parafunctional, clinical-history, traumatic, and lifestyle correlates. Methods This cross-sectional study included 884 questionnaire records from an eligible population of 1481 dental students at Biruni University, Istanbul, Türkiye, yielding a 59.7% response rate. The questionnaire included demographic variables, academic year, the 10-item FAI, and study-specific 0–10 or yes/no self-report items. Complete FAI data were available for 878 students. Nonparametric comparisons, chi-square tests, Spearman correlations, and exploratory multivariable logistic regression were performed. Benjamini–Hochberg false-discovery-rate (FDR) adjustment was applied to 20 univariable tests. Results The mean FAI score was 29.9 ± 20.2. FAI screening categories were none in 263 students (30.0%), mild in 397 (45.2%), moderate in 171 (19.5%), and severe in 47 (5.4%); 218 students (24.8%) had moderate-to-severe symptom burden. Female students had higher FAI scores than males (32.9 ± 20.5 vs. 25.2 ± 19.0; p < 0.001; FDR q < 0.001), whereas scores did not differ by academic year ( p = 0.616; q = 0.649). The strongest correlations involved self-perceived TMJ problems, morning head/neck pain, morning masticatory muscle fatigue/pain, and pre-existing joint pain/clenching (ρ = 0.49–0.54; all q < 0.001). In the exploratory adjusted model, morning head/neck pain, morning masticatory muscle fatigue/pain, and pre-existing joint pain/clenching remained positively associated with moderate-to-severe FAI symptom burden. These symptom-related covariates conceptually overlap with FAI components and should be interpreted as concurrent correlates rather than independent risk factors. Conclusions FAI-screened symptoms suggestive of TMD were common among dental students, with approximately one quarter showing moderate-to-severe symptom burden. These estimates represent screening-defined symptom burden rather than clinically confirmed TMD prevalence or clinical severity. The observed associations are cross-sectional and exploratory and support further studies using standardized clinical TMD assessment and validated psychosocial measures.